Urinary Calcium/Creatinine Ratio in the Prediction of Preeclampsia - Winit Phuapradit (2018)
Summary: The prediction of preeclampsia by the urinary calcium/creatinine ratio during the early third trimester was assessed in 190 primigravidas, aged less than 35 years and between 28 and 32 weeks' gestation without pregnancy complications. Preeclampsia developed in 6.8% of the patients. The mean maternal age, gestational age at entry into the study and at delivery, and the average mean arterial blood pressure at entry into the study did not differ significantly between the 13 patients with subsequent preeclampsia and the 177 normotensive patients. The patients with preeclampsia did not have significantly less excretion of calcium than the normotensives. Copyright © 1993, Wiley Blackwell. All rights reserved